The Activity of Unfractionated Heparin and Low Molecular Weight Heparins in Rabbit Plasma – The Need for Using Absolute Anti-factor Xa and Antithrombin Activities - Peyrou, V; Béguin, S; Boneu, B; Hemker, H C (Thrombosis and Haemostasis, 1997)
Rabbit being a common animal model to evaluate the antithrombotic effect of heparins, our purpose was to apply the heparin Standard Independent Unit (SIU) approach to rabbit plasma. To take into account the specificities of the enzymes we have measured the decay constants of factor Xa and of thrombin from autologous and heterologous origins, in presence and in absence of heparin. Different heparins or heparin fractions with a mean molecular weight from 1.7 to 10.5 kDa were used.We found that: a) the decay constants varied strongly between species and between enzymes; b) the decay constants of thrombin were always higher than those of factor Xa; c) the specific anti-factor Xa activity of heparins increased with the molecular weight and was 1.33 times higher when determined with bovine factor Xa than with rabbit factor Xa; d) the specific antithrombin activity of heparins also increased with the molecular weight but was similar when determined with rabbit and human thrombin; e) the specific anti-factor Xa activity was always lower than the specific antithrombin activity; f) the calibration of the heparins and heparin fractions against the 4th International Standard of Heparin expressed in International Units (IU) lead to a systematic overestimation of the anti-factor Xa activity and to an underestimation of the antithrombin activity.These observations indicate that it may be very important to use the SIU approach and to know the accurate activities to better understand the mechanism of the antithrombotic activity of heparins in experimental models.